Integration of Basic Competencies, Methods, and Assessment in Arabic Language Lesson Plans at Madrasah Aliyah: a Qualitative Study - Ade Arip Ardiansyah; Resti Namira Wulandari; Moh Alhan Faiz Alby Anway (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the integration of basic competencies, instructional methods, and assessment components in Arabic language lesson plans (RPP) at Madrasah Aliyah. The research employs a descriptive qualitative approach to provide an in-depth description of how basic competencies, teaching methods, and assessment are integrated within Arabic language lesson plans in the Madrasah Aliyah context. Primary data were obtained through interviews, observations, and document analysis of the lesson plans, while secondary data were derived from curriculum guidelines, textbooks, policy documents, and relevant studies. Data were collected through semi-structured interviews, documentation, and limited classroom observations. The analysis followed the Miles and Huberman model, data reduction, data display, and conclusion drawing, supported by triangulation to ensure the validity of findings. The study seeks to produce a comprehensive overview of the quality of component integration within lesson plans as implemented in practice. The findings indicate that the integration of basic competencies, instructional methods, and assessments in Arabic language lesson plans at Madrasah Aliyah remains weak. Basic competencies are listed formally, yet the indicators are not measurable, resulting in limited guidance for method selection and assessment design. Teachers tend to rely on generic, teacher-centered methods, while communicative approaches are rarely implemented. Assessment emerges as the weakest component, as performance-based instruments such as speaking (kalam) and listening (istima’) tests are seldom utilized. The lack of alignment among components highlights the need for improved teacher competence, intensive training, mentoring in lesson-plan development, and strengthened supervision to ensure more effective instructional planning.